The association between longer haemodialysis treatment times and hospitalization and mortality after the two-day break in individuals receiving three times a week haemodialysis. Issue 9 (28th February 2019) - Fotheringham, James; Sajjad, Ayesha; Stel, Vianda S; McCullough, Keith; Karaboyas, Angelo; Wilkie, Martin; Bieber, Brian; Robinson, Bruce M; Massy, Ziad A; Jager, Kitty J
Abstract: Background: On the first haemodialysis (HD) day after the 2-day break in three times a week (3×W) in-centre HD, mortality and hospitalization are higher. If longer HD sessions prescribed 3×W is associated with a reduction in these events is unknown. Methods: HD session length in 19 557 prevalent European in-centre 3×W HD patients participating in the Dialysis Outcomes and Practice Patterns Study (1998–2011) were categorized into <200, 200–225, 226–250 or >250 min. Standardized event rates on the first (HD1) versus the second (HD2) HD day after the 2-day break, with supporting Cox proportional hazards models adjusted for patient and dialysis characteristics, were generated for all-cause mortality, all-cause hospitalization, out-of-hospital death and fluid overload hospitalization. Results: By comparing HD1 with HD2, increased rates of all endpoints were observed (all P < 0.002). As HD session lengthened across the four groups, all-cause mortality per 100 patient-years on the HD1 (23.0, 20.4, 16.4 and 14.6) and HD2 (26.1, 13.3, 13.4 and 12.1) reduced. Similar improvements were observed for out-of-hospital death but were less marked for hospitalization endpoints. However, even patients dialysing >250 min were at significantly greater risk on HD1 when compared with their HD2 for out-of-hospital death [hazard ratio (HR) = 2.1, 95% CI 1.0–4.3], all-cause hospitalization (HR = 1.3, 95% CI 1.2–1.4) and fluid overload hospitalization (HR = 3.2, 95% CI 1.8–6.0). Conclusions: Despite the association between reduced mortality across all dialysis days in patients performing longer sessions, elevated risk on the first dialysis day relative to the second persists even in patients dialysing 4.5 h 3×W.